Destabilization of Akt Promotes the Death of Myeloma Cell Lines. (28th August 2014) - Zhang, Yanan; Fu, Yunfeng; Zhang, Fan; Liu, Jing
Abstract : Constitutive activation of Akt is believed to be an oncogenic signal in multiple myeloma and is associated with poor patient prognosis and resistance to available treatment. The stability of Akt proteins is regulated by phosphorylating the highly conserved turn motif (TM) of these proteins and the chaperone protein HSP90. In this study we investigate the antitumor effects of inhibiting mTORC2 plus HSP90 in myeloma cell lines. We show that chronic exposure of cells to rapamycin can inhibit mTORC2 pathway, and AKT will be destabilized by administration of the HSP90 inhibitor 17-allylamino-geldanamycin (17-AAG). Finally, we show that the rapamycin synergizes with 17-AAG and inhibits myeloma cells growth and promotes cell death to a greater extent than either drug alone. Our studies provide a clinical rationale of use mTOR inhibitors and chaperone protein inhibitors in combination regimens for the treatment of human blood cancers.